The Periodic Instability of Diameter of ZnO Nanowires via a Self-oscillatory Mechanism - Zhang Ye; Yan Youguo; Zhu Feng (Nanoscale Research Letters, 2007)
Abstract ZnO nanowires with a periodic instability of diameter were successfully prepared by a thermal physical vapor deposition method. The morphology of ZnO nanowires was investigated by SEM. SEM shows ZnO possess periodic bead-like structure. The instability only appears when the diameter of ZnO nanowires is small. The kinetics and mechanism of Instability was discussed at length. The appearance of the instability is due to negative feed-back mechanism under certain experimental conditions (crystallization temperature, vapor supersaturation, etc).